The rink hockey goalkeeper: somatic characteristics and activity profile - Sousa, Tiago Emanuel da Costa e (2021)
Thesis for the degree of Doctor in Sport Sciences in the branch of Sports Training supervised by Prof. Dr. Vasco Vaz and Prof. Dr. Hugo Sarmento, submitted to the Faculty of Sport Sciences and Physical Education of the University of Coimbra